The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/2013jc009381
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biological controls on DMS,P dynamics in ice shelf-influenced fast ice during a winter-spring and a spring-summer transitions

Abstract: We report the seasonal and vertical variations of dimethylsulfide (DMS) and its precursor dimethylsulfoniopropionate (DMSP) in fast ice at Cape Evans, McMurdo Sound (Antarctica) during the springsummer transition in 2011 and winter-spring transition in 2012. We compare the variations of DMS,P observed to the seasonal evolution of the ice algal biomass and of the physical properties of the ice cover, with emphasis on the ice texture and brine dynamics. Isolated DMS and DMSP maxima were found during both seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 107 publications
(209 reference statements)
6
63
2
Order By: Relevance
“…Historically, studies on Antarctic fast ice algal communities have focused primarily on the taxonomy and physiology of algae inhabiting high‐biomass microhabitats (Arrigo et al, ; Grossi et al, ; McMinn, Pankowskii, et al, ; Stoecker et al, ; Whitaker & Richardson, ). Time series studies have been conducted in specific regions but overall remain sparse (Carnat et al, ; Delille et al, ; Fiala et al, ; Günther & Dieckmann, ; Watanabe et al, ). Here we compiled a comprehensive database of ice algal Chl a concentrations from Antarctic fast‐ice cores collected from different regions around the continent.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, studies on Antarctic fast ice algal communities have focused primarily on the taxonomy and physiology of algae inhabiting high‐biomass microhabitats (Arrigo et al, ; Grossi et al, ; McMinn, Pankowskii, et al, ; Stoecker et al, ; Whitaker & Richardson, ). Time series studies have been conducted in specific regions but overall remain sparse (Carnat et al, ; Delille et al, ; Fiala et al, ; Günther & Dieckmann, ; Watanabe et al, ). Here we compiled a comprehensive database of ice algal Chl a concentrations from Antarctic fast‐ice cores collected from different regions around the continent.…”
Section: Introductionmentioning
confidence: 99%
“…Keller et al, 1989;Stefels, 2000), environmental forcing are known to control DMSP, DMSO, and DMS concentrations. In ice-associated environments, brine volume fraction might also be key in explaining DMS cycling variability via the control of ice permeability (Carnat et al, 2014). Structural changes within sea ice during the melt season, namely increases in brine volume fraction and ice desalination, result in increased connectivity and permeability in the warming sea ice (Willis et al, 2016;Polashenski et al, 2012) and influence DMSP and DMS cycling Carnat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In ice-associated environments, brine volume fraction might also be key in explaining DMS cycling variability via the control of ice permeability (Carnat et al, 2014). Structural changes within sea ice during the melt season, namely increases in brine volume fraction and ice desalination, result in increased connectivity and permeability in the warming sea ice (Willis et al, 2016;Polashenski et al, 2012) and influence DMSP and DMS cycling Carnat et al, 2014). Also, phytoplankton blooms developing under the ice during the melting period have been shown to produce large quantities of DMSP p , potentially leading to a build-up of DMS concentrations (Levasseur et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The lower 50 mm of each, plus attached platelets, was cut off using a stainless steel hacksaw, and transferred to a shore laboratory in a dark, insulated box for processing within 2 h. Previous studies have shown that this length of the cut section of the core contains the majority of the chla biomass (>99% authors' unpublished data; see also Ryan et al, 2006, Carnat et al, 2014. Cores were imaged and characteristics of the ice core, specifically the presence or absence of embedded 25 platelets, whether algae were primarily interstitial within the congelation ice or associated with platelets, and whether the core itself appeared to have been recovered with or without some degree of damage to the ice undersurface, was recorded.…”
Section: Methodsmentioning
confidence: 99%